Vapor-liquid equilibrium data for binary mixtures of dimethyl carbonate with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate at 93.13 kPa - Mali, Nilesh A.; Yadav, Satyajeet S.; Ghuge, Pravin D.; Joshi, Sunil. S. (Journal of Chemical and Engineering Data, 2017)
Isobaric vapor-liquid equilibrium (VLE) data was measured at the local atmospheric pressure of 93.13 kPa for the binary systems of dimethyl carbonate (DMC) with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate using a dynamic recirculation still. VLE data was generated in the form of T-x,y and was checked for thermodynamic consistency using the Herington area test, Van Ness test, and mean absolute deviation between experimental and calculated total pressure and vapor phase composition. Data for all pairs meet the criteria for thermodynamic consistency and were found suitable for process modeling. Binary interaction parameters for the Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models were determined using the objective function of minimizing the deviation between the experimental and the calculated vapor phase composition and total pressure. For all binary systems, Wilson, NRTL, and UNIQUAC models gave good predictions. Azeotropic behavior was observed for the isopropyl acetate-DMC pair at 357.8 K and 0.6 mole fraction of isopropyl acetate.

Refractive index and vapor-liquid equilibrium data for the binary systems of anisole with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
Phase equilibrium behavior of binary systems of anisole with xylene isomers was analyzed experimentally. An apparatus which establishes equilibrium conditions through continuous circulation of equilibrium vapor condensate and equilibrium liquid was used. Experimental data comprising refractive indices of binary mixtures, equilibrium compositions of vapor and liquid, and equilibrium temperature are reported for all binary systems. Thermodynamic consistency of vapor-liquid equilibrium data was established for using the Herington, Van Ness and absolute mean deviation tests. Interaction parameters of activity coefficient models, Wilson, nonrandom two liquid, and universal quasichemical, which are important for accounting nonideal behavior in process modeling, are also estimated through regression of the respective binary VLE data. Although VLE data shows that binary systems are nonazeotropic in nature, a pinch in the T-x,y plot indicates that separation of all binary system using distillation may need a significant number of stages.

Experimental vapor-liquid phase equilibrium analysis of the binary systems of aniline with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2020)
In the present work, vapor-liquid phase equilibrium (VLE) analyses of binary systems of aniline with four isomers of xylene, comprising p-xylene, m-xylene, o-xylene, and ethylbenzene, are reported at 93.13 kPa. The experimental VLE data was generated in a dynamic circulating vapor-liquid, and the data was found thermodynamically consistent using the Van Ness point-to-point consistency test. The experimental VLE data was regressed with the Wilson, NRTL, and UNIQUAC activity coefficient models to obtain the binary interaction parameters. No azeotropic or close-boiling behavior was observed in any of the binary pair, and these pairs were found suitable for separation through a conventional distillation method.